Workplace Violence towards Healthcare Workers: An Italian Cross-Sectional Survey - Nicola Ielapi; Michele Andreucci; Umberto Marcello Bracale; Davide Costa; Egidio Bevacqua; Nicola Giannotta; Sabrina Mellace; Gianluca Buffone; Vito Cerabona; Franco Arturi; Michele Provenzano; Raffaele Serra (MDPI AG, 2021)
Background. Workplace violence (WPV) is a major healthcare problem with important consequences in healthcare areas and may impact negatively not only healthcare workers but also the quality and safety of patient care. Objectives: This an observational online web-based survey using Google® Modules, specifically aiming to investigate the phenomenon of WPV in Italian healthcare services. Methods. Data collection for this study lasted one month, with the questionnaire available from 1 May 2021 to 31 May 2021. Continuous variables were considered as either mean ± standard deviation (SD) or median and interquartile range (IQR) based on their distribution. Comparison between groups was assessed by unpaired t-test or Mann-Whitney U test according to variable distribution. Categorical variables were analyzed using the chi-squared test. Results. The study population consisted of 203 healthcare workers, represented by nurses (61.6%), medical doctors (16.8%), patient care assistants (4.9%), and others (16.7%). Female gender was associated with a 2.6 times higher risk for the presence of aggression (p = 0.034), and nurse as a job with about 4 times increased risk for the presence of aggression (p = 0.006). The risk for aggression increased by 5% for each year of work experience. Conclusions. WPV is still matter of concern in Italian healthcare services. A strong organizational effort is demanded from healthcare institutions in order prevent internal and external violence in healthcare settings.